Description of a new species of the genus Pycanum (Hemiptera: Heteroptera:Tessaratomidae: Tessaratomini) from India with comments and key to extant species of the genus - Ghate, Hemant V.; More, Sadashiv; Magnien, Philippe (Zootaxa, 2020)
A new species of a tessaratomid bug, namely Pycanum occidentale sp. nov, is described with comments on the other species of the genus found in India. This species can be easily distinguished from the other species of Pycanum by the shape of male genitalia, especially pygophore and parameres. This becomes the fourth species of Pycanum in India and the first one from western India. A key to the extant species of the genus is also provided along with diagnostic images of pygophores and parameres for three species found in India.